2018
DOI: 10.1186/s12935-018-0607-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of galectin-1 expression in patients with cancer: a meta-analysis

Abstract: BackgroundThe prognostic significance of galectin-1 (Gal-1) expression in cancerous patients has been assessed for several years while the results remain controversial. Thus, we performed the first comprehensive meta-analysis to evaluate the prognostic value of Gal-1 expression in cancerous patients.MethodsWe searched Pubmed, Embase and Web of Science to recruit studies on the prognostic impact of Gal-1 expression in cancerous patients. Eighteen studies containing 2674 patients were involved in this meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…Galectin-1 (LGALS1) is a member of the carbohydrate-binding protein family, which shares a conserved amino acid sequence in the carbohydrate recognition domain and shows high affinity for β-galactoside-containing glycol-conjugates [5,6]. Several studies have demonstrated that LGALS1 plays an important role in tumorigenesis, progression and metastasis of human cancers [7], serving as a reliable diagnostic and prognostic biomarker in cancerous patients [8,9]. For instance, Schulkens et al [10] have observed that LGALS1 expression in non-small cell lung cancer tissues was elevated compared with adjacent normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Galectin-1 (LGALS1) is a member of the carbohydrate-binding protein family, which shares a conserved amino acid sequence in the carbohydrate recognition domain and shows high affinity for β-galactoside-containing glycol-conjugates [5,6]. Several studies have demonstrated that LGALS1 plays an important role in tumorigenesis, progression and metastasis of human cancers [7], serving as a reliable diagnostic and prognostic biomarker in cancerous patients [8,9]. For instance, Schulkens et al [10] have observed that LGALS1 expression in non-small cell lung cancer tissues was elevated compared with adjacent normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, MG‐63 cells were grown in 60 mm cell culture dishes, treated with 6n for 48 hr and the supernatant was collected. As Gal‐1 is an extracellular secreted protein, its expression can be quantified from the cellular external environment (Wu et al., ). Equal amounts of supernatant were subjected to quantitative enzyme immunoassay as per manufacture's protocol (DGAL10, R&D Systems).…”
Section: Resultsmentioning
confidence: 99%
“…There are many similar and recent studies that support our findings. Wu [19] observed that high galectin-1 expression was associated with poor OS in digestive cancers. Wang [20] suggested that galectin-3 plays an oncogenic role, and is expressed in colorectal cancer, non-small cell lung cancer and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%